2019
DOI: 10.1016/j.jses.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of screw length and screw quantity on reverse total shoulder arthroplasty glenoid fixation for 2 different sizes of glenoid baseplates

Abstract: BackgroundLittle guidance exists regarding the minimum screw length and screw quantity necessary to achieve fixation in reverse total shoulder arthroplasty (rTSA); to that end, this study quantified the displacement of 2 different sizes of glenoid baseplates using multiple different screw lengths and quantities of screws in a low-density polyurethane bone-substitute model.MethodsTesting of rTSA glenoid loosening was conducted according to ASTM F 2028-17. To independently evaluate the impact of screw quantity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…A longer individual screw length has been shown to provide significantly better baseplate fixation after cyclic loading, regardless of the number of screws used. 22 The post hoc planning in this study alleviates potential concerns that the surgeons used fewer screws for the sole purpose of obtaining significant results. We cannot draw any biomechanical conclusions based on these data, but these results do reflect a significant change in practice at our institution because of intraoperative navigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A longer individual screw length has been shown to provide significantly better baseplate fixation after cyclic loading, regardless of the number of screws used. 22 The post hoc planning in this study alleviates potential concerns that the surgeons used fewer screws for the sole purpose of obtaining significant results. We cannot draw any biomechanical conclusions based on these data, but these results do reflect a significant change in practice at our institution because of intraoperative navigation.…”
Section: Discussionmentioning
confidence: 99%
“…Computer-assisted intraoperative navigation and preoperative planning software applications in rTSA have only recently been described in the orthopedic literature because of the relative infancy of the technology. 21 , 22 , 27 Patient-specific instrumentation and 3-dimensional (3D) imaging and templating technologies improve the accuracy of glenoid component placement in accordance with a preoperative plan. 1 , 3 , 12 , 20 , 26 , 27 In addition, 3D templating may increase the accuracy of screw placement relative to the preoperative plan.…”
mentioning
confidence: 99%
“…On the other hand, Dharia et al 29 found that the combination of 2 screws (1 superior and 1 inferior) resulted in higher micromotion than a combination using 4 peripheral screws (superior, anterior, inferior and posterior). Roche et al 30 found that the average displacement with 2 screws was significantly greater than that with 4 screws in both the antero-posterior and supero-inferior cyclic loading, while no differences were observed in displacement before and after cyclic loading between the 4- and 6-screw configurations in either the supero-inferior or antero-posterior direction. Conversely, James et al 31 compared the use of 2 (superior and inferior) and 4 screws and found no significant differences between these 2 groups in micromotion and displacement.…”
Section: Discussionmentioning
confidence: 98%
“…Initial fixation of the baseplate is essential for long-term stability [28][29][30] . Longer baseplate screws have been demonstrated to improve glenoid baseplate fixation 31,32 . The inferior screw is the most important for fixation because the tensile load is applied to the inferior aspect of the glenoid prosthesis 33 .…”
Section: Discussionmentioning
confidence: 99%